2019
DOI: 10.3345/kjp.2019.00220
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between genetic heterogeneity and variability for response to growth hormone in Noonan syndrome

Abstract: See the article "Comparison of effectiveness of growth hormone therapy according to diseasecausing genes in children with Noonan syndrome" in Volume 62 on page 274.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Up to 70% of NS subjects present with postnatal short stature ( 17 , 37 ), even though the majority has a normal birth weight and length ( 20 ); the presence of edema may result in an overestimation of weight which should be carefully evaluated ( 20 ). Some authors have reported a significantly higher frequency of NS subjects who are small for gestational age (SGA) compared with the general population (24%), particularly for length ( 24 ), and in specific genotypes ( 24 , 38 ).…”
Section: Growth and Growth Hormone-igf-1 Axis In Noonan Syndromementioning
confidence: 99%
See 4 more Smart Citations
“…Up to 70% of NS subjects present with postnatal short stature ( 17 , 37 ), even though the majority has a normal birth weight and length ( 20 ); the presence of edema may result in an overestimation of weight which should be carefully evaluated ( 20 ). Some authors have reported a significantly higher frequency of NS subjects who are small for gestational age (SGA) compared with the general population (24%), particularly for length ( 24 ), and in specific genotypes ( 24 , 38 ).…”
Section: Growth and Growth Hormone-igf-1 Axis In Noonan Syndromementioning
confidence: 99%
“…As NS is a condition characterized by clinical variability and genetic heterogeneity, different mechanisms implicated with altered GH secretory dynamics or response have been reported, including GHD, neurosecretory dysfunction, and GH insensitivity (GHI) ( 17 , 21 ). Decreases in IGF-I and IGF-binding protein 3, together with low responses to provocation tests, suggest impaired GH release, or disturbance of the GH/IGF-I axis, at least in a proportion of affected individuals ( 21 ).…”
Section: Growth and Growth Hormone-igf-1 Axis In Noonan Syndromementioning
confidence: 99%
See 3 more Smart Citations